Bilateral skin temperature drop and warm sensibility decrease following modulation of body part ownership through mirror-box illusion. (February 2021) - Crivelli, Damiano; Polimeni, Elisa; Crotti, Daniele; Bottini, Gabriella; Salvato, Gerardo
Abstract: The implicit and explicit awareness of owning a body and its parts is a constant accompaniment in our everyday life and our interaction with the outside world. The way in which we build and maintain a coherent sense of body ownership is not fully understood. It has been postulated that the integration between exteroceptive, interoceptive, and proprioceptive signals may play a fundamental role in the sense of body ownership. For instance, studies on healthy subjects and brain-damaged patients have suggested that alterations in the sense of body ownership are coupled with autonomic signal changes, such as thermoregulatory reactions. However, the available evidence is conflicting, possibly due to shortcomings in the experimental paradigm that previous studies have adopted. In this study, we explore the relationship between body ownership, thermoregulation, and thermal sensitivity through a novel application of the mirror-box illusion paradigm, overcoming some of the limitations of previous studies. We find a bilateral decrease in hand skin temperature, together with reduced thermal sensitivity for warm thermal stimuli following the induction of the illusion of ownership towards the participant's reflected hand. These findings demonstrate the importance of the orchestration of exteroceptive (e.g., visual), autonomic (e.g., body temperature) and proprioceptive (e.g., position and movement of the body) signals in maintaining a coherent sense of body ownership.